The Governance Effect: Unpacking Operational Risk Disclosure through Board Attributes and Institutional Ownership - Anggraeni, Dian Yuni (Jurnal Sosial Humaniora, 2026)
This research aims to determine the influence of board characteristics and institutional ownership on operational risk disclosure of Indonesian Islamic Banks for 2017 – 2021. The research was conducted using the Pooled Least Square (PLS) method involving 15 Sharia Commercial Banks in Indonesia in 2017-2021. The results of this study show that the size of the board of directors has a positive effect on operational risk disclosure. In contrast, the size of the sharia supervisory board, the size of the board of commissioners, and institutional ownership do not affect operational risk disclosure. These findings have implications for policymakers and regulators of Islamic commercial banks regarding the development and implementation of the influence of board characteristics and institutional ownership that can improve operational risk disclosure. This research contributes to meeting the needs and increasing understanding of the influence of board character and institutional ownership. This can help Islamic commercial banks engage in effective compliance when carrying out operational risk disclosures.